2008
DOI: 10.1007/s11434-008-0083-1
|View full text |Cite
|
Sign up to set email alerts
|

A physically-based statistical forecast model for the middle-lower reaches of the Yangtze River Valley summer rainfall

Abstract: A new approach to forecast the middle-lower reaches of the Yangtze River Valley summer rainfall in June-August (JJA) is proposed in this paper. The year-to-year increment of the middle-lower reaches of the Yangtze River Valley is forecasted and hence the summer precipitation could be predicted. In this paper, DY is defined as the difference of a variable between the current year and the preceding year (year-to-year increment). YR denotes the seasonal mean precipitation rate of the middle-lower reaches of the Y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
98
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 127 publications
(100 citation statements)
references
References 13 publications
(14 reference statements)
2
98
0
Order By: Relevance
“…Moreover, multi-decadal variation of Asian summer climate in recent decades has been noticed (e.g., Wang 2001;Jiang and Wang 2005;Wang et al 2008;Fan et al 2008;Huang et al 2013Huang and Li 2015;Xu et al 2015;Zhu et al 2011). Particularly, many studies have found the significant decadal shift of the interannual variability of Asian summer climate in the 1990s.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, multi-decadal variation of Asian summer climate in recent decades has been noticed (e.g., Wang 2001;Jiang and Wang 2005;Wang et al 2008;Fan et al 2008;Huang et al 2013Huang and Li 2015;Xu et al 2015;Zhu et al 2011). Particularly, many studies have found the significant decadal shift of the interannual variability of Asian summer climate in the 1990s.…”
Section: Introductionmentioning
confidence: 99%
“…In order to resolve such climate prediction difficulties, we developed an inter-annual increment prediction approach [9,10]. With our approach the predicted result is a year-to-year increment of a variable (e.g.…”
Section: Citationmentioning
confidence: 99%
“…Unlike synoptic process studies of snowstorms [2][3][4][5] and their climatic characteristics [1,7], climate prediction of snowstorm activity in this region is rare. This is because inter-annual variability of Northeast snowstorm activity and predictive dynamic climate models are ineffective on high latitude climates [8].In order to resolve such climate prediction difficulties, we developed an inter-annual increment prediction approach [9,10]. With our approach the predicted result is a year-to-year increment of a variable (e.g.…”
mentioning
confidence: 99%
“…After adding the predicted WHD NCP DY to the observed WHD NCP of the previous year, the interdecadal and socioeconomic components were contained in the final prediction. In prior studies, the DY approach has been used to explore the prediction of summer rainfall in China (Fan et al, 2008), heavy winter snow activity in northeast China (Fan and Tian, 2013), summer Asian-Pacific Oscillation (Huang et al, 2014) and winter North Atlantic Oscillation (Tian and Fan, 2015). Furthermore, some variables cross influenced by socioeconomic and climatic factors were predicted successfully using the DY approach, e.g., rice production in northeast China (Zhou and Wang, 2014) and the discoloration day for Cotinus coggygria leaves in Beijing .…”
Section: Introductionmentioning
confidence: 99%